The Functions of the Demonstrative Pronouns in the Sentences in the Kurdish- Badini Local Dialect - ali, dilbreen abdullah (Humanities Journal of University of Zakho, 2018)
The study shows the functions of the demonstrative pronouns in the Kurdish sentences which are used in the Bahdini local dialect. The aim of using the demonstrative pronouns is to refer to people or things without mentioning their names. Those pronouns are used with the help of specific parts of the body such as; fingers, hands, eyebrows, etc.When we use or move a part of our body to refer to a person or a thing, the demonstrative pronouns can be easily identified. They are mainly used to refer to something which is either near or far from us. The research has a theoretical part and a practical part. In the theoretical part, except for the demonstrative pronouns, grammarians used different terms to refer to demonstrative pronouns, after that, they had been defined by grammarians. Besides, in this part, the demonstrative pronouns are being precisely shown in the sentences of the Kurdish Bahdini local dialect. By contrast, the practical part of the study presentsthe fundamental functions of the demonstrative pronouns in the sentences, these functions are; subject, direct object, indirect object and the complement of the verb. Finally, the research concludes that demonstrative pronouns can have various functions.